Novel Word Learning Among Bilinguals Can Be Better Through the (Dominant) First Language Than Through the Second Language. Issue 4 (10th July 2021) - Hirosh, Zoya; Degani, Tamar
Abstract: When learning novel vocabulary in a third language (L3) through translations in the first language (L1), bilinguals may have more available cognitive resources and more accumulated experience in language regulation compared to when learning through translations in the second language (L2). In a study designed to test language of instruction (LOI) effects, 59 Hebrew–English bilinguals auditorily learned over two sessions 55 words in German, including three word types: cognates, overlapping in form and meaning between English and German; false cognates, overlapping in form but not meaning; and controls. Critically, half of the participants learned through their (dominant) L1 Hebrew, and half through their L2 English (which is also more similar to German). Results showed a significant LOI effect, with better learning through the (less similar) L1, especially for control items. Cognates were learned better in both LOIs, but false cognates were learned better relative to controls to a greater extent when the LOI was English. Together, results highlight the importance of LOI and item‐based language similarity during multilingual novel word‐learning. Abstract :